Poor sleep is associated with higher blood pressure and uterine artery pulsatility index in pregnancy: a prospective cohort study - Tang, Y; Zhang, J; Dai, F; Razali, NS; Tagore, S; Chern, BSM; Tan, KH (BJOG : an international journal of obstetrics and gynaecology, 2021)
Objective To elucidate the association between sleep disturbances and blood pressure as well as uterine artery Doppler during pregnancy in women with no pre‐existing hypertension. Design Prospective cohort study. Setting Outpatient specialist clinics at KK Women’s and Children’s Hospital, Singapore. Population Women with viable singleton pregnancies confirmed by ultrasonography at less than 14 weeks of amenorrhoea at first visit. Methods In all, 926 subjects were recruited for this study in the outpatient specialist clinics at KK Women’s and Children’s Hospital, Singapore, between 1 September 2010 and 31 August 2014. They were followed up throughout pregnancy with sleep quality, blood pressure and uterine artery Doppler assessed at each visit. Main outcome measures Sleep quality, blood pressure and uterine artery Doppler. Results Sleep progressively worsened as pregnancy advanced. Shorter sleep duration and poorer sleep efficiency were associated with higher blood pressure, especially in the first trimester. Mixed model analysis demonstrated an overall positive association between sleep quality represented by Pittsburgh Sleep Quality Index (PSQI) score and diastolic blood pressure (DBP) (P < 0.001) and mean arterial pressure (MAP) (P = 0.005) during pregnancy after considering all trimesters. Sleep duration was found to be negatively associated with both systolic blood pressure (SBP) (P = 0.029) and DBP (P = 0.002), whereas sleep efficiency was negatively correlated with DBP (P = 0.002) only. Overall poor sleep during pregnancy was also found to be associated with a higher uterine artery pulsatility index. Conclusion Our prospective study demonstrated that poor sleep quality is significantly associated with higher blood pressure and uterine artery pulsatility index during pregnancy. Tweetable Poor sleep quality is significantly associated with higher blood pressure and higher uterine artery pulsatility index during pregnancy. Tweetable Poor sleep quality is significantly associated with higher blood pressure and higher uterine artery pulsatility index during pregnancy.